Coupled effect of substrate and light on assimilation and oxidation of regenerated nitrogen in the euphotic ocean. (11th February 2019) - Xu, Min Nina; Li, Xiaolin; Shi, Dalin; Zhang, Yao; Dai, Minhan; Huang, Tao; Glibert, Patricia M.; Kao, Shuh‐Ji
Abstract: Nitrogen (N), as a critical element for microbial metabolisms, recycles rapidly in the euphotic ocean. Oxidation by nitrifiers is a competing pathway for phytoplankton assimilation of regenerated N (NH4 + and urea). Sharing the overlapping substrates may result in competitive exclusion, thus, niche separation for the two assemblages. Both pathways are sensitive to light, but whether light intensity will intensify or alleviate such resource competition in the euphotic zone remains poorly explored in the field at the community level. By using 15 N labeling techniques, paired kinetic responses of uptake and oxidation were conducted in single bottles under manipulated light intensities for both NH4 + and urea. We found light stimulated the maximum rate ( R m ) and specific affinities ( α U ) of both NH4 + and urea uptake. In contrast, light effects were opposite for oxidation kinetics ( R m and α O ). As irradiance increased, the rapid increase in α U and concomitant decrease in α O imply a distinctive competition advantage of photosynthetic organisms over oxidizers under substrate‐limited environments. The ratio of α U / α O for NH4 + ranged from 0.8 to 3089 (5.8–46, 788 for urea) showing a distinct increasing pattern as ambient light increases, demonstrating that phytoplankton overwhelms nitrifiers throughout the oligotrophic euphotic zone, driving down concentrations and maintaining short turnover times of the two regenerated N substrates. Moreover, phytoplankton relied equally on NH4 + and urea; yet, nitrifiers preferred NH4 + to urea. In the nitrate‐depleted euphotic ocean, light acts as a crucial driver for utilization pathways of regenerated N and vertical niche separation.